The Enigma of the Tinnitus-Free Dream State in a Bayesian World - Dirk De Ridder; Kathleen Joos; Sven Vanneste (Neural Plasticity)
There are pathophysiological, clinical, and treatment analogies between phantom limb pain and phantom sound (i.e., tinnitus). Phantom limb pain commonly is absent in dreams, and the question arises whether this is also the case for tinnitus. A questionnaire was given to 78 consecutive tinnitus patients seen at a specialized tinnitus clinic. Seventy-six patients remembered their dreams and of these 74 claim not to perceive tinnitus during their dreams (97%). This can be most easily explained by a predictive Bayesian brain model. That is, during the awake state the brain constantly makes predictions about the environment. Tinnitus is hypothesized to be the result of a prediction error due to deafferentation, and missing input is filled in by the brain. The heuristic explanation then is that in the dream state there is no interaction with the environment and therefore no updating of the prediction error, resulting in the absence of tinnitus.